Media Pembelajaran : Pengembangan Media Pembelajaran melalui Google Sites untuk Memperbaiki Keterampilan Membaca Siswa pada Teks Recount - Supriyadi, Hermawan; Rukmini, Dwi; Ruminda, Ruminda (Inovasi: Jurnal Diklat Keagamaan, 2025)
In the digital era, teachers are expected to design enjoyable learning process in the classroom. This is especially true for schools with good facilities and resources for developing teaching materials. A teacher should creatively and innovatively design lessons to facilitate students' understanding of the material delivered by the teacher. The first step is to adapt the teaching method to the characteristics of the students and use an easily accessible Learning Management System. Additionally, enjoyable teaching materials can increase students' interest and prevent boredom. Google Sites is one way to create and manage a website. With Google Sites, users can create websites without learning complex programming languages or web design, as the tool provides various user-friendly features and templates.The development of online or offline teaching materials is expected to provide optimal benefits for the teaching and learning process. This research aims to explain how the Google Sites platform is developed as a teaching medium, how it is implemented as a teaching medium, and to describe students' responses to English language lessons using Google Sites concerning reading skills. The research methodology used is qualitative descriptive. The research object uses media, which is called Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The validation results conducted by experts are 88.45%, with the category "very valid." Meanwhile, the student response to the use of the media is 66.89%, categorized as “fairly good”. Based on both results, it can be concluded that using the media is quite effective in teaching and learning activities for reading skills.